Behind the Italian regional divide: An economic fitness and complexity perspective - Angelica Sbardella; Andrea Zaccaria; Luciano Pietronero; Pasquale Scaramozzino (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2021)
This paper applies the Economic Fitness and Complexity approach to analyse the underlying factors behind the wide and persistent economic disparities across the Italian regional units. Measures of regional fitness are obtained from their revealed comparative advantage and from their patent performance. Southern regions tend to be characterised by a lower level of complexity than the regions in the Centre-North of the country. We interpret these results as indicating a lower level of capability endowment in the South. The system-wide approach of the paper is able to identify some critical sectors which display a rich pattern of connections with other sectors and which could play a pivotal role to create additional capabilities and foster a more balanced regional development.
Keywords: L60; O11; O14; O47; 330; Italian regional divide; Economic Fitness and Complexity; Productive and technological capabilities